An efficient barrier toward vanadium crossover in redox flow batteries: The bilayer [Nafion/(WO3)x] hybrid inorganic-organic membrane. (10th May 2021) - Sun, Chuanyu; Negro, Enrico; Nale, Angeloclaudio; Pagot, Gioele; Vezzù, Keti; Zawodzinski, Thomas A.; Meda, Laura; Gambaro, Chiara; Di Noto, Vito
Abstract: A family of hybrid inorganic-organic ion-exchange membranes (IEMs) is prepared, indicated as [Nafion/(WO3 )x ]. The IEMs consist of Nafion® dispersing different loadings (x) of tungsten oxide nanofiller. Morphology studies carried out by scanning electron microscopy (SEM) and micro-Raman investigations reveal that one side of each hybrid IEM exhibits a high concentration of the WO3 nanofiller. In the remaining part of each IEM the concentration of the filler is much lower and constant. The correlation between the asymmetrical nature and the performance of the hybrid IEMs is studied in a single-cell vanadium redox flow battery (VRFB). In comparison with the Nafion 212 reference, at the same current density of 50 mA∙cm −2, [Nafion/(WO3 )0.587 ] demonstrates: (i) a higher Coulombic efficiency (93% vs. 88%), a higher energy efficiency (75% vs. 65%) and a higher capacity retention (62% vs. 42%).